Investigation of carbon cathode surface before and after the passage of combined DC vacuum arc with superimposed high-current arc pulses - Zavaleyev, V.; Walkowicz, J.; Moszyński, D. (Вопросы атомной науки и техники, 2016)
The paper presents the results of studies of carbon cathode surface before and after the passage of the combined DC vacuum-arc with superimposed high-current arc pulses. Investigations of surface morphology of carbon cathode showed, that secondary nuclei of high-density are formed after passing of the combined DC-pulse vacuum-arc, which results in the formation of a globular structures. The phase structure analysis by Raman spectroscopy showed that even at a minimum operation time (5 s) of the combined DC-pulse vacuum-arc broadening of the peaks 1355 and 1583 cm⁻¹ occurs, which means that the carbon cathode surface undergo phase transformation. Results obtained by XPS spectroscopy demonstrate that the globular structures formed on the cathode surface are composed of sp³-bonded carbon atoms and carbon-oxygen bonds.